Systems Analysis for Water Technology - Gujer, Willi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book presents in a concise format the methods used to develop mathematical models for water and wastewater treatment. It provides a systematic approach to mass balances, transport and transformation processes, kinetics, stoichiometry, reactor hydraulics, residence time distribution, heterogeneous systems, and the dynamic behaviour of reactors. In addition it includes an introduction to parameter identification, error analysis, error propagation, process control, time series analysis, stochastic modelling and probabilistic design. Written as a textbook it is primarily intended to support graduate and doctoral students in environmental engineering, but may also serve as a valuable resource for academics and practitioners alike.
Modeling and Simulation -- System Boundaries and Material Balances -- Transport Processes -- Transformation Processes -- Ideal Reactors -- Hydraulic Residence Time Distribution -- Modeling of Real Reactors -- Heterogeneous Systems -- Dynamic Behavior of Reactors -- Measurement and Measurement Uncertainty -- Parameter Identification, Sensitivity and Error Propagation -- Process Control Engineering -- Time Series Analysis -- Design under Uncertainty -- Problems.
Keywords: Water pollution; Water-supply.; Engineering geology; Engineering—Geology.; Foundations; Hydraulics; Civil engineering; Mechanical engineering; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Industry/Water Technologies; Geoengineering, Foundations, Hydraulics; Civil Engineering; Mechanical Engineering